(untitled) (Global Journal of Science Frontier Research, 2014)
Production of α-amylase enzyme by Bacillus Lichenoformis using stirred tank fermentor (BIOSTAT -E) was carried out. The strain was obtained from National Chemical Laboratory, Pune, India. Corn starch is used as the substrate. The enzyme production was studied by changing the various parameters like temperature, pH, rpm and substrate concentration. The biomass cell concentration shows maximum at a temperature of 35 0 C -37 0 C, pH 8 and 300 rpm. The maximum enzyme production was achieved, for 1% concentration of cornstarch at 35 0 C and pH 8 using the fermentation medium contains yeast extract and peptone and the cell concentration was found to be 2.882 gm dry weight/lit. Since the cost of yeast extract and peptone is very high, so the further work was done using some low cost carbon and nitrogen sources like defatted cotton seed, defatted soya flour and mustard seed which are extracted from agricultural byproducts.